Faktor-Faktor Utama Nilai Perusahaan: Ukuran Perusahaan, Leverage, Dan Profitabilitas - Dewi Ratnasari Astuti; Rizky, Rizky Ridwan; Fitri Nurlaila (LPPM POLITEKNIK LP3I BANDUNG, 2024)
How the size, leverage, and profitability of a company affect its value is the purpose of this study. Firm value is an assessment made by investors to determine the level of success of a company, and is usually correlated with stock prices. In this case, company size, profitability, and leverage are some of the factors that affect its value. 21 LQ45 companies listed on the Indonesia Stock Exchange (IDX) in 2022 were sampled. The results showed that the firm size variable was positively and significantly influenced by firm value, the leverage variable was positively and significantly influenced by firm value, and profitability was negatively and significantly influenced. according to the results of the t test.